The Expanding Role of the Counsellor: Fitting Means to Ends - Dumont, Florent; Torbit, Gary (Canadian Journal of Counselling and Psychotherapy, 2012)
This article is intended to stimulate debate on 1) the political implications ofthe counselling act; 2) the various and expanding roles and services that may be appropriate to the counselling profession in contemporary North America; 3)and some salient concerns of those attempting to forge new settings for the delivery of those services.